ПОПУЛЯЦІЙНА СТРУКТУРА І УМОВИ ФОРМУВАННЯ ПРОМИСЛОВОГО ЗАПАСУ ХАМСИ ENGRAULIS ENCRASICOLUS У ПОБЕРЕЖЖЯ КРИМУ В ОСІННЬО-ЗИМОВИЙ СЕЗОН 2007/2008 РР - Зуєв, Г. В.; Гуцал, Д. К.; Репетін, Л. Н.; Салехова, Л. П.; Мельнікова, О. Б.; Бондарев, В. А.; Мурзін, Ю. Л. (Marine Ecological Journal, 2023)
Intraspecific status of anchovy wintering in 2007/2008 years near south and south-west Crimean coast was studied. Anchovy attribution to the Black Sea population was determined using index of otoliths. The dynamics of size-age and sex structures of anchovy population in autumn-winter season and catch dynamics were analyzed. Hydrometeorological factors causing anchovy autumnal migration to Crimean coastal area were discussed.